Decreased DNA methylation in the promoter region of the WNT5A and GDNF genes may promote the osteogenicity of mesenchymal stem cells from patients with ossified spinal ligaments - Noriyuki Chiba; Ken-Ichi Furukawa; Shohei Takayama; Toru Asari; Shunfu Chin; Yoshifumi Harada; Gentaro Kumagai; Kanichiro Wada; Toshihiro Tanaka; Atsushi Ono; Shigeru Motomura; Manabu Murakami; et al. (Elsevier, 2015)
Mesenchymal stem cells (MSCs) isolated from spinal ligaments with ectopic ossification have a propensity toward the osteogenic lineage. To explore epigenetic control of the osteogenic features of MSCs, we treated MSCs obtained from the spinal ligaments of ossification of yellow ligament (OYL) patients and non-OYL patients with the DNA methyltransferase inhibitor, 5-aza-2'-deoxycytidine (5AdC). We compared the non-OYL groups (untreated and treated with 5AdC) with the OYL groups (untreated and treated with 5AdC) by genome-wide microarray analysis. Next, we used methylated DNA immunoprecipitation combined with quantitative real-time PCR to assess gene methylation. Ninety-eight genes showed expression significantly increased by 5AdC treatment in MSCs from non-OYL patients but not from OYL patients. In contrast, only two genes, GDNF and WNT5A, showed significantly higher expression in OYL MSCs compared with non-OYL MSCs without 5AdC treatment. Both genes were hypermethylated in non-OYL MSCs but not in OYL MSCs. Small interfering RNA targeted to each gene decreased expression of the target gene and also several osteogenic genes. Both small interfering RNAs also suppressed the activity of alkaline phosphatase, a typical marker of osteogenesis. These results suggest that the osteogenic features of MSCs from OYL patients are promoted by unmethylated WNT5A and GDNF genes.